2010
DOI: 10.1007/s10482-010-9527-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Penicillium digitatum and Penicillium italicum in vitro and in planta with Panomycocin, a novel exo-β-1,3-glucanase isolated from Pichia anomala NCYC 434

Abstract: Panomycocin, a novel exo-beta 1,3 glucanase, was tested as an antifungal agent against green and blue mold diseases, the most important causes of post harvest decay in citrus fruits. All tested isolates of Penicillium digitatum and Penicillium italicum were susceptible to panomycocin in vitro. Effective panomycocin concentrations for 50% growth inhibition (MIC-2) for P. digitatum and P. italicum were 2 and 1 microg ml(-1), respectively. Complete (MIC-0) growth inhibition of all isolates observed at a panomycoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Since the cell wall is one of the most common sites of action of toxins, different components can be found acting as receptors of killer toxins, such as β-1,3-D-glucans, β-1,6-D-glucans, mannoproteins and chitin [ 114 ]. Some known toxins produced by yeasts are: (i) PMKT and PMKT2, produced by Pichia membranifaciens , which bind, respectively, to β-1,6-D-glucans and mannoproteins of the cell wall of pathogens [ 115 ]; (ii) panomycocin, produced by a strain of P. anomala , which exerts its activity by hydrolyzing β-1,3-glucans [ 116 ]; (iii) zymocin, produced by Kluyveromyces lactis , which hydrolyzes chitins present in the fungal cell wall acting as antifungal components [ 117 ]. It should be noted that only a small fraction of the recognized killer toxins has been so far characterized in detail [ 105 ].…”
Section: Yeasts As Biocontrol Against Fungal Pathogenic Microorganismsmentioning
confidence: 99%
“…Since the cell wall is one of the most common sites of action of toxins, different components can be found acting as receptors of killer toxins, such as β-1,3-D-glucans, β-1,6-D-glucans, mannoproteins and chitin [ 114 ]. Some known toxins produced by yeasts are: (i) PMKT and PMKT2, produced by Pichia membranifaciens , which bind, respectively, to β-1,6-D-glucans and mannoproteins of the cell wall of pathogens [ 115 ]; (ii) panomycocin, produced by a strain of P. anomala , which exerts its activity by hydrolyzing β-1,3-glucans [ 116 ]; (iii) zymocin, produced by Kluyveromyces lactis , which hydrolyzes chitins present in the fungal cell wall acting as antifungal components [ 117 ]. It should be noted that only a small fraction of the recognized killer toxins has been so far characterized in detail [ 105 ].…”
Section: Yeasts As Biocontrol Against Fungal Pathogenic Microorganismsmentioning
confidence: 99%
“…Yeast W. anomalus WA45 demonstrated the production of β-glucanases (mycocins) and antimicrobial activity. Mycocins, which have little or no toxicity to human erythrocytes, and are low in resistance, are being studied as potential candidates for antimicrobial development (Izgu et al, 2011;Paris et al, 2016).…”
Section: Microdilution Test and Antimicrobial Potential Of Mycocinsmentioning
confidence: 99%
“…digitatum and P . italicum even after 5–7 days of incubation [25]. Moreover, Platania et al [23] reported the biological control of P .…”
Section: Discussionmentioning
confidence: 99%
“…This killer activity can be defined as the ability of some yeast to secrete protein toxins or low molecular mass glycoproteins that are lethal to other susceptible yeasts [21] as well as to filamentous fungi and bacteria [22,23,24]. Various yeasts with such phenotype have shown high efficiency in the control of Penicillium and other pathogenic fungi that cause postharvest infections in fruits such as lemons, oranges and papaya [22,23,25]. However so far there was no work on isolation of indigenous killer yeasts for biological control in citrus of this region, which would have adaptive advantages for the vast production of lemons in Tucumán.…”
Section: Introductionmentioning
confidence: 99%